Challenges in implementing green campus initiatives in the Malaysian Public Universities / Ahmad Afiq Mohd Muhiddin ... [et al.] - Mohd Muhiddin, Ahmad Afiq; Mohd Isa, Haryati; Md Sakip, Siti Rasidah; Janah Singh, Daljeet Singh Sedhu (2022)
The direction toward sustainability has become the most crucial issue globally, including in higher education institutions, due to its responsibility to produce future leaders of the nation. Therefore, the university should seriously play its role toward realizing environmental sustainability. Consequently, numerous Malaysian public universities have begun to take this issue seriously. However, there are several challenges encountered. This paper aims to examine green campus implementation in Malaysian public universities. Thus, the main objective is to determine the challenges faced by Malaysian public universities in implementing green campus initiatives. Semi-structured interviews with the senior Green Campus representatives from three Malaysian public universities were conducted, and the findings were analyzed using content analysis. The research revealed that although most Malaysian public universities had implemented green initiatives indicators outlined in the UI GreenMetric Guideline 2022, numerous challenges occurred. Some of the challenges are repetitively for numerous indicators. Among the challenges identified are limited spaces and infrastructures, lack of finance, lack of knowledge and awareness among campus communities, lack of support from the university management and stakeholders, lack of green campus implementation frameworks and policies, lack of well-coordinated team, limited economical options on water saving system, bureaucracy, uncertain climate and weather conditions, lack of safe and adequate infrastructure provided for cyclists and pedestrians in the campus, lack of interest and engagement among campus communities on sustainable environment education program and frequent restructuring of subordinates or top management positions. The research posits the necessity of developing new ways of thinking by all related parties to face the challenges relating to the green campus implementation as this initiative can provide various benefits towards realizing Sustainable Development Goals, as well as assuring more sustainable practices in the future.